General Practitioners’ Perceptions of Collaboration with Pharmacists in Primary Care Settings: A Study Driven by Social Capital Theory and Theory of Planned Behavior - Gabby Lovarya; Yosi Irawati Wibowo; Adji Prayitno Setiadi (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2026)
Background: Pharmacists are expected to take up broader clinical roles and collaborate with general practitioners (GPs); however, data on the perception of GPs’ in the primary care settings is lacking.Objective: This study aimed to explore GPs’ perceptions driven by Theory Planned Behavior (TPB) and Social Capital Theory (SCT) towards collaboration with pharmacists in primary care settings.Methods: Interviews using questionnaires (with a combination of open-and closed-ended questions) were conducted with GPs at all Puskesmas in East Surabaya (n=14). Descriptive analysis was used to summarize data from closed-ended questions, and thematic analysis was used for open-ended questions.Results: A total of 28 GPs of 14 Puskesmas were included (i.e., 2 GPs per Puskesmas). The mean scores of each dimension for intrapersonal perceptions (based on TBP): 1) attitude (2.6 – positive); 2) subjective norms (3.3 – positive), 3) difficulty (2.75 – low). While the mean scores for interpersonal perceptions (based on SCT): 1) level of trust (5.7 – high); 2) level of social capital (6.0 – high). There were five themes for basic trusts: i) daily performance, ii) pharmacy skills and knowledge, iii) work experience, iv) performance track records, v) ability to communicate and collaborate with GPs. This study highlighted while GPs generally have positive perceptions, some items warrant considerations, such as negative experience with pharmacists (39.3%), lack of support from management (92.9%), and perceived difficulty to practice collaboration due to workload, cost and facilities. Additionally, 42.9% of GPs reported that they cannot fully trust delegating work to pharmacists.Conclusions: Findings from this study should provide guidance to develop strategies to optimize collaborative practice with GPs, thus facilitating the expanded clinical roles of pharmacists in primary care settings.